2021
DOI: 10.21608/assjm.2021.195345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arbuscular Mycorrhizal Fungi And Some Phosphorus Sources on Growth, Seeds Yield, Chemical Compositions, Oil Productivity and Fixed Oil Constituents of Chia (Salvia hispanica L.) Plant

Abstract: This study was conducted at the Experimental farm of the Heliopils University, El Sharqea, Egypt during the two successive seasons of 2016/2017 and 2017/2018. The aim of this study was to investigate the possibility of improving growth, seed yield, oil productivity and fixed oil constituents of chia (Salvia hispanica L.) plants grown in sandy soil by using arbuscular mycorrhizal fungi (AMF) and some phosphorus sources i.e., phosphate rock -super phosphate -monoamonium phosphate (MAP) and phosphoric acid (30 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…(Buee et al, 2000;Lohse et al, 2005). Similar results of mycorrhizal fungi were obtained by Moghith et al, (2021) on (Salvia hispanica L.) plants. Mohamed (2020) on Dutch fennel.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…(Buee et al, 2000;Lohse et al, 2005). Similar results of mycorrhizal fungi were obtained by Moghith et al, (2021) on (Salvia hispanica L.) plants. Mohamed (2020) on Dutch fennel.…”
Section: Discussionsupporting
confidence: 78%
“…The majors components of chia oil was stated by various studies like Ayerza and Coates (2005) found that the major component were α-linolenic (63.2%), linoleic (18%), oleic (3.4%), palmitic (7.25%) and stearic (3.4%); Segura-Campos et al (2014) stated that chia oil contains αlinolenic (68.52%), linoleic (20.40%), oleic (2.43%), palmitic (7.74%) and stearic (0.29%) and Silva et al (2016) studied quantification of fatty acids in the chia seed oils obtained with different solvents and stated that α-linolenic arranged (61.48 -62.92%), linoleic (18.10 -19.76%), oleic (6.9 -6.87%), palmitic (9.13 -9.95) and stearic (2.92 -2.99%). Moghith et al (2021) declared that the main components were αlinolenic acid (54.96 to 63.23%) linoleic acid (15.82 to 21.36), oleic acid (6.19 to 15.86%) and palmitic acid (6.30 to 8.15%). Mohamed and Ghatas (2020) on chia declared that the main component was α-linolenic acid (37.28 to 39.72%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the application of the triple combined treatments (Az + B.c + AM) proved to be more effective in elevating fixed oil % as reached 8.5 and 8.5% over untreated plants, during the two successive seasons, respectively. The primitive influence of Azotobacter chroococcum on fixed oil was also obtained on by El-Houssini (2009) on borage; Hamad (2007) on guar; by Mohamed et al (2020), Abd El-moneim (2023 on Nigella sativa concerning Bacillus circulans and on sunflower (Abdallah et al, 2013), on flax Dawood et al (2019), Abou El-Ghait et al (2021, Moghith (2021) on chia regarding mycorrhiza. It worthy mention that the interaction between the two studied factors on fixed oil % of borage had significant effect, during the two seasons (Table 6).…”
Section: Fixed Oil Percentagementioning
confidence: 82%